2019
DOI: 10.21831/pg.v14i1.25067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prerequisite concepts understanding and mathematical communication skills toward student’s mathematical proving ability

Abstract: This study aims to describe the influence of prerequisite concepts understanding and mathematical communication skills on the mathematical proving ability of Mathematics Education Program students in the Faculty of Mathematics and Science, State University of Jakarta (FMIPA UNJ). The method used in this study was a survey and correlational techniques. The study population was all students of the Mathematics Education Program FMIPA UNJ in 2018. The study sample was taken with a simple random sampling technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
(11 reference statements)
3
6
0
Order By: Relevance
“…This research further demonstrates that they have greater efficacy because they apply their findings to real-world issues while utilizing natural language and mathematical jargon in their research (Hutapea et al, 2019;Palinussa, 2013). The researchers also discovered something else interesting: students with stronger communication skills in mathematics were better at verifying a mathematical theorem, which matched the conclusions of the study of Salsabila (2019). This finding corroborates the ideas of Zhou et al (2021), who suggested that incorporating good communication skills into the context of a mathematical argument increases students' overall ability to perform well.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This research further demonstrates that they have greater efficacy because they apply their findings to real-world issues while utilizing natural language and mathematical jargon in their research (Hutapea et al, 2019;Palinussa, 2013). The researchers also discovered something else interesting: students with stronger communication skills in mathematics were better at verifying a mathematical theorem, which matched the conclusions of the study of Salsabila (2019). This finding corroborates the ideas of Zhou et al (2021), who suggested that incorporating good communication skills into the context of a mathematical argument increases students' overall ability to perform well.…”
Section: Discussionmentioning
confidence: 58%
“…In the exercise part, students are quite economical in presenting and explaining but only focus on the results of the problem, thereby having difficulty in solving problems related to reality or explaining a problem; this result is also similar to the study of Sudia and Muhammad (2020). Additionally, most students still have difficulty presenting their ideas and solutions orally, have confusion, lack confidence, and choose inappropriate expressions (Salsabila, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some supporting capabilities are needed in this regard. In accordance with the results of the study from [6], it is necessary to have good mathematical understanding and communication skills in overcoming student difficulties in proofing. This can be overcome by designing learning activities that can provide opportunities for students to represent and communicate their mathematical ideas, according to the research results of [7].…”
Section: Introductionmentioning
confidence: 76%
“…The group set out to develop high-quality and cutting-edge instruments as a means of improving the reliability of the findings from the research. Two prominent experts in the field of mathematics education agreed that the evaluations were valid, and this method was also used successfully in the research by Salsabila (2019). Following the completion of the evaluation and subsequent adjustments, the research and the instruments were put into action.…”
Section: Data Processingmentioning
confidence: 99%
“…Most notably, one can argue regardless of whether or not the conclusion desired by the listener is correct. The correctness or incorrectness of a student's reasoning does not matter when it comes to proving or disproving counterexamples (Salsabila, 2019). This suggests that the debate is more broadly about the process of discovering mathematical proofs than it is about any particular proofs in particular.…”
Section: Introductionmentioning
confidence: 99%